Penerapan Algoritma Taboo Codes Pada Kompresi File Text - Naomi Yuni Intan Hutagalung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The needs of modern humans and the demands of technological developments today force every individual to work a lot on computers and use all digital data, requiring everyone to use a text file manager application such as Microsoft Office to process a conventional text into a digital text file. This is because files in digital electronic form are preferred over conventional forms, due to certain factors such as data security problems, ease of processing, distribution and modification of data. The tendency of humans at this time to collect data in the form of text files and documents on a computer causes storage media on computer devices to run out faster. Moreover, at this time most individuals share text files using internet media via email or social media such as WhatsApp and telegram, meanwhile the very slow internet network in Indonesia causes the sending of large text files to take a very long time. The Taboo Codes algorithm has an approximation to the length of a variable. The initiator of the Taboo Codes Algorithm is Steven Pigeon, the principle of the Taboo Codes Algorithm, which is to select positive n numbers and reverse the n pattern to indicate the end of the code, the taboo codes algorithm works to compress text files by replacing the original binary value of each character into a binary value. The taboo codes algorithm is shorter, so compressing a text file using the taboo codes algorithm can reduce the original text file size by about 20%.